The Development of Scientific Imagineering Learning Activity through Facebook to Enhance Learners’ Key Competencies - Techakosit, S.; Srisakuna, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
The development of Learners’ Key Competencies (LKCs) is one of the goals of the primary education core curriculum that is currently being used in Thailand. Therefore, learning activities that enhance LKCs are essential for all teachers. The objectives of this research were to develop a Scientific Imagineering (SIG) learning activity through Facebook in enhancing LKC development and to study its effectiveness. A research and development method was used in this study. A total of 30 students of grade 11 which selected using purposive sampling participated in the learning activity. A self-assessment of LKCs form was used to investigate the situation in a physics class, before and after participation in the learning activity. The research results showed that SIG learning activity through Facebook consisted of six steps in the form of Imagine, Study, Design, Develop, Present, and Evaluate. The evaluation results by five experts concerning the suitability of this learning activity indicated that it could be used to enhance LKCs and had great potential to be implemented. Comparing the students’ self-assessment with regard to LKCs, it was clear that there was a significant overall increase (p<.05). The comparison of students’ self-assessment to the LKCs for each component also found that the skills of communication, thinking and learning, problem-solving, and technological application increased significantly (p<.05). The results of this study support the view that SIG learning activity through Facebook could enhance the LKCs of students.